Gendered Relationship of Childbearing with Earnings Accumulated by Midlife in Two Nordic Welfare States - Nisén, Jessica; Erlandsson, Anni; Jalovaara, Marika (Springer Nature, 2025)
The Nordic welfare states are considered advanced in terms of gender equality, but even in these countries women still take longer family leave and have lower earnings than men. This study provides new insights by assessing the differences in accumulated midlife earnings associated with childbearing between women and men in Finland and Sweden. We pay particular attention to the size of the gender gap in accumulated earnings across groups. We hypothesize that the gender gap will be larger among those with a larger number of children, among those with a lower level of education, and overall in Finland. The study is based on complete population register data, with highly accurate measures of earnings over decades. Our results show that by the age of 44, women born in 1974–1975 in Finland and Sweden had earned on average 32% and 29% less than men, respectively. Childbearing strongly modifies the gender gap, especially in Finland, and the highly educated have moderately smaller gaps in both countries. Our results show that, even the Nordic welfare states, despite their strong policy emphasis on gender equality and their success in achieving high levels of female labor force participation, are far from closing the gender gap in earnings accumulated over the first half of the life course. Our results also suggest that governments seeking to achieve gender equality should be cautious about providing long family-related leave with flat-rate compensation.